The Effect of Information Technology on Quality Management and Employee Performance of the Jember University Library (International Journal of Scientific Research and Management (IJSRM), 2019)
One of the factors in question is human resources (HR). The quality and advantages issued by each individual (HR) are expected to contribute to the progress of the organization. Contributions to the progress of the organization in accordance with the opinion of Titisari, Purnamie et al. (2016) "an organization that is always developing is everyone’s hope. Both the government and the private sector expect their organizations to grow and develop well. This development is expected to enable organizations to compete, which cannot accelerate with the progress of this organization to be left behind”. This study focuses on developing information technology on employee performance, developing quality management on employee performance and developing information technology on quality management. The Jember University Library which will be used as an object in this study has long implemented a quality management system and implementation of information technology in all processes carried out. The object of the research was conducted in the Library with a sample of 46 employees. The data source used is a questionnaire which is primary data and secondary data such as the list of employees and the organizational structure of the University Library of Jember. Varies using a Likert scale. The analytical tool used uses SmartPLS 3.0. In this study obtained results produced by Quality Management (X2) on Employee Performance (Y1) has a path coefficient value of 0.419 and its effect is significant (t = 2.897, p = 0.004) because t> 1.96; p <0.005. The Effect of Information Technology (X1) on Employee Performance (Y1) has a path coefficient value of 0.456 and its effect is significant (t = 3.188, p = 0.002) because t> 1.96; p <0.005. The Influence of Information Technology (X1) on Quality Management (X2) has a path coefficient value of 0.853 and its effect is significant (t = 21.597, p = 0,000) because t> 1.96; p <0.005. Thus it can be concluded that Ha is accepted because of t-statistics> 1.96. Approved with the value of probability it can be concluded that Ha is accepted because p <0.05.